Potential treatment approaches for malignant peritoneal mesothelioma: in vivo and in vitro experimental study of natural killer cell immunotherapy - Heliang Wu; Yi Wang; Yulin Lin; Ru Ma; Xuemei Du; Yandong Su; Rui Yang; Zhiran Yang; Xinli Liang; Yinguang Zhang; Xiaoqing Liang; Zhonghe Ji; et al. (Cancer Biology & Medicine, 2024)
Objective: Malignant peritoneal mesothelioma (MPM) is a rare primary malignant tumor with an extremely poor prognosis that currently lacks effective treatment options. This study investigated the in vitro and in vivo efficacy of natural killer (NK) cells for treatment of MPM. Methods: An in vitro study was conducted to assess the cytotoxicity of NK cells from umbilical cord blood to MPM cells with the use of a high-content imaging analysis system, the Cell Counting Kit-8 assay, and Wright–Giemsa staining. The level of NK cell effector molecule expression was detected by flow cytometry and enzyme-linked immunosorbent assays. The ability of NK cells to kill MPM cells was determined based on live cell imaging, transmission electron microscopy, and scanning electron microscopy. An in vivo study was conducted to assess the efficacy and safety of NK cell therapy based on the experimental peritoneal cancer index, small animal magnetic resonance imaging, and conventional histopathologic, cytologic, and hematologic studies. Results: NK cells effectively killed MPM cells through the release of effector molecules (granzyme B, perforin, interferon-γ, and tumor necrosis factor-α) in a dose- and density-dependent manner. The NK cell killing process potentially involved four dynamic steps: chemotaxis; hitting; adhesion; and penetration. NK cells significantly reduced the tumor burden, diminished ascites production, and extended survival with no significant hematologic toxicity or organ damage in NOG mice. Conclusions: NK cell immunotherapy inhibited proliferation of MPM cells in vitro and in vivo with a good safety profile.